Photographs depicting CSR: captured reality or creative illusion?. Issue 3 (31st May 2019) - Chong, Sabrina; Narayan, Anil K.; Ali, Irshad
Abstract : Purpose: The purpose of this study is to uncover the extent of utilisation of photographs depicting corporte social responsibility (CSR) information in corporate annual reports and the possible motives for their use. Design/methodology/approach: The study used visual content analysis, based on Banks' (2001) strategy of "looking through", "looking at" and "looking behind" photographic images, to examine and analyse 4, 933 photographs contained in the 2005, 2010 and 2015 annual reports of 70 companies listed on New Zealand Stock Exchange. The findings were interpreted using the impression management theoretical construct. Findings: The findings show a marked increase in the utilisation of photographs for CSR-associated disclosures by the sample companies. Surprisingly, the quantity of photographs depicting environmental performance has declined, whereas those featuring product responsibility have increased significantly. The "messages" encoded in the photographs create idealistic images of the companies being caring and responsible corporate citizens. This suggests that companies are systematically using symbolic presentations such as photographs of children and families for rhetorical impression management. Practical implications: The study contributes to a greater understanding of the power of photographs in representing and constructing "reality" of CSR performance. The findings have the potential to inform and assist the promulgation of guidelines for CSR reporting, as well as make users aware that photographs could be exploited as a rhetoric and impression management tool in pursuit of symbolic legitimacy. Originality/value: The study develops a structured approach for categorising and analysing CSR-related photographs and adds to the scant literature on the utilisation of photographs as a medium for CSR information dissemination.